Recreational noise induced hearing loss: South African undergraduate students’ perspectives - Khoza-Shangase, Katijah; Mokhethi, Khothatso (Frontiers in Public Health, 2025)
BackgroundRecreational noise-induced hearing loss (NIHL) is an increasing public health concern among young adults who frequently use personal listening devices (PLDs) at high volumes for extended periods. Despite this, awareness of NIHL risks remains low, particularly among university students in South Africa.ObjectiveThis study aimed to assess undergraduate students’ awareness of recreational NIHL, examining their earphone use habits, volume preferences, preventive behaviors, and associations between demographic variables and NIHL awareness.MethodsA cross-sectional survey was conducted with 154 undergraduate students at a large urban South African university. Quantitative data on listening habits, NIHL awareness, and preventive behaviors were collected and analysed using descriptive including thematic analysis and inferential statistics such as Chi-square tests to examine associations between variables.ResultsMost participants (67.5%) reported daily earphone use, often at moderate (48.1%) or high (33.8%) volumes. Awareness of NIHL was low, with only 9.7% of students feeling very informed. Inferential analysis revealed significant associations between NIHL awareness and age (χ2 = 12.67, p < 0.05), as well as year of study (χ2 = 10.89, p < 0.05), with older students and those in upper academic years (third year or beyond) showing greater awareness. Preventive behaviors were inconsistent; 46.1% of students reported lowering volume, while 13.0% took no preventive measures. Further analysis revealed that students who preferred high volumes were more likely to adopt preventive measures, while those who preferred low volumes often took no action, perceiving their existing habits as safe. Thematic analysis identified concerns about hearing health, barriers to safe listening, influence of social norms, and misconceptions about ear health.ConclusionThe findings highlight a high prevalence of potentially unsafe listening behaviors and low NIHL awareness among South African university students. Recommendations include university-based hearing health programs, leveraging social media for outreach, integrating education into first-year curricula, and promoting affordable protective options, and social media campaigns targeting safe listening practices. These measures could help foster safer listening habits and reduce NIHL risk within this vulnerable population.